2012
DOI: 10.1177/0267659111434857
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation following pediatric cardiac surgery: development and outcomes from a single-center experience

Abstract: Extracorporeal membrane oxygenation (ECMO) has emerged as an effective mechanical support following cardiac surgery with respiratory and cardiac failure. However, there are no clear indications for ECMO use after pediatric cardiac surgery. We retrospectively reviewed medical records of 76 pediatric patients [mean age, 10.8 months (0–86); mean weight, 5.16 kg (1.16–16.5)] with congenital heart disease who received ECMO following cardiac surgery between January 1997 and October 2010. Forty-five patients were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
(20 reference statements)
1
20
0
1
Order By: Relevance
“…ECLS allows transportation of patients in cardiopulmonary collapse and bridging of critically ill patients to be recovered. There have been no agreed criteria that can be used to predict the need for ECLS support in the perioperative/postoperative period and mostly clinical judgment is defined as what we rely on, when evaluating potential patients (8,9). However, Belohlavek et al reported increased mortality rate during ECLS run in the patients with higher Sequential Organ Failure Assessment score (10).…”
Section: Discussionmentioning
confidence: 99%
“…ECLS allows transportation of patients in cardiopulmonary collapse and bridging of critically ill patients to be recovered. There have been no agreed criteria that can be used to predict the need for ECLS support in the perioperative/postoperative period and mostly clinical judgment is defined as what we rely on, when evaluating potential patients (8,9). However, Belohlavek et al reported increased mortality rate during ECLS run in the patients with higher Sequential Organ Failure Assessment score (10).…”
Section: Discussionmentioning
confidence: 99%
“…Early use of mechanical support may reverse the progression of organ failure and lead to shorter duration of ECMO and increased patient survival (2). The definition of maximal treatment varies in these circumstances but includes adequate circulating blood volume, adequate hemoglobin, and a large amount of inotropic drugs.…”
Section: Indications For Ecmomentioning
confidence: 99%
“…Mechanical circulatory support systems have successfully improved clinical outcomes in patients with cardiac and respiratory dysfunctions (1). Extracorporeal membrane oxygenation (ECMO) is widely used for respiratory and circulatory support, especially in critical cases such as acute cardiac dysfunction, cardiac resuscitation, and acute respiratory distress syndrome (2)(3)(4).…”
mentioning
confidence: 99%